Monitoring Behaviorally Induced Biochemical Changes Using Fluorescence Lifetime Photometry - Lee, Suk Joon; Chen, Yao; Lodder, Bart; Sabatini, Bernardo L. (Frontiers in Neuroscience, 2019)
All cells respond to extracellular signals by altering their intracellular biochemical state. In neurons, such signaling regulates many aspects of cell and synapse biology and induces changes that are thought to be important for nervous system development, its adaptation in the face of a changing environment, and ongoing homeostatic maintenance. Although great advances have been made in developing novel fluorescent reporters of intracellular signaling as well as in methods of fluorescence detection for use in freely moving animals, these approaches have generally not been combined. Thus, we know relatively little about how the intracellular biochemical state of neurons, and other cell classes, is dynamically regulated during animals’ behavior. Here we describe a single multi-mode fiber based fluorescent lifetime photometry system (FLiP) designed to monitor the state of fluorescence reporters of biochemical state in freely moving animals. We demonstrate the utility of FLiP by monitoring the lifetime of FLIM-AKAR, a genetically encoded fluorescent reporter of PKA phosphorylation, in populations of direct and indirect pathway striatal projection neurons in mice receiving food rewards. We find that the activity of PKA in each pathway is transiently regulated by reward acquisition, with PKA phosphorylation being enhanced and repressed in direct and indirect pathway neurons, respectively. This study demonstrates the power of FLiP to detect changes in biochemical state induced by naturalistic experiences in behaving animals.